A fracturing proppant using magnesium-aluminum material as raw material and preparation method thereof
By using modified magnesium-aluminum hydrotalcite and other components in fracturing proppants, the problem of high and difficult firing temperature of magnesium-aluminum materials is solved, and the high compressive strength and low density of the ceratops are achieved, which improves the Fracturing effect.
Patent Information
- Application Number
- CN202310679907.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-06-08
AI Technical Summary
After the introduction of magnesium-aluminum materials, the firing temperature is high and the firing is difficult, resulting in a decrease in the mechanical properties of the ceramic particles.
Use bauxite, cooked alumina, coal gangue and other components with modified magnesium-alumina hydrotalcite to fill the pores of mullite lattice under high temperature sintering conditions to form a sponge framework structure and microporous structure to reduce sintering Temperature and difficulty.
It effectively reduces the sintering temperature of the ceramic fracturing proppant, improves the compressive strength and mechanical properties of the ceramic, and is suitable for promotion and application.
Smart Images

Figure HDA0004276117410000011 
Figure HDA0004276117410000012
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fracturing proppants, and more specifically, to a fracturing proppant using magnesium-aluminum material as raw material and a preparation method thereof. Background Art
[0002] Oil fracturing technology refers to a reservoir transformation technology that uses hydraulic force to form artificial cracks in oil and gas layers, thereby improving the flow capacity of fluids in oil and gas layers. The specific technical principle is roughly as follows: using a ground high-pressure pump group, a large-displacement, high-viscosity liquid is injected into the formation through the wellbore to build up high pressure at the bottom of the well. When the pressure exceeds the bearing capacity of the formation, cracks will form in the formation. Continue to inject liquid carrying fracturing proppants, and the cracks will gradually extend forward. The fracturing proppants play a role in supporting the cracks, so that the cracks opened by the fracturing will not close again, and then form sand-filled cracks with a certain size and high conductivity, so that oil and gas can easily flow into the well through the cracks, achieving the effect of increasing production and injection.
[0003] It can be seen that the compressive resistance of fracturing proppants has a great influence on the effect of increasing production and injection. Commonly used fracturing proppants include: quartz sand, walnut shells, artificial ceramsite, artificial plastic balls, artificial glass balls, etc., among which quartz sand and artificial ceramsite are the most widely used. Artificial ceramsite contains components such as alumina, silicate and iron oxide, has high strength and density, can withstand high pressure, and can meet the fracturing requirements of various types of well depths and well conditions.
[0004] The higher the strength of the fracturing proppant, the higher the density and the faster the sedimentation rate. If it settles too early in the formation, it will be difficult to form a long propped crack, which will affect the fracturing effect. To address this problem, technicians have developed low-density and high-strength fracturing proppants, usually by introducing components such as magnesium aluminum, red mud, fly ash, bentonite, etc. into the raw materials of ceramsite proppants to achieve both low density and high strength performance.
[0005] For fracturing proppants that introduce magnesium-aluminum components, since magnesium-aluminum materials have a high melting point, the firing temperature during the production process is high, the firing is difficult, and the poor crystal phase structure formed leads to a decrease in the mechanical properties of the ceramsite sintered body. Summary of the invention
[0006] In order to improve the problem of poor mechanical properties caused by high sintering temperature and great sintering difficulty after the introduction of magnesium-aluminum materials, the present application provides a fracturing proppant using magnesium-aluminum materials as raw materials and a preparation method thereof.
[0007] In the first aspect, the present application provides a fracturing proppant using magnesium-aluminum material as raw material, adopting the following technical solution:
[0008] A fracturing proppant using magnesium-aluminum material as raw material is made of the following raw materials by weight percentage:
[0009] Bauxite 50-60%;
[0010] Jadeite 20-30%;
[0011] Coal gangue 3-5%;
[0012] Modified magnesium aluminum hydrotalcite 8-10%;
[0013] Iron ore 4-6%;
[0014] The remainder is waste ceramsite;
[0015] The modified magnesium aluminum hydrotalcite is prepared by a method comprising the following steps:
[0016] 1) Take magnesium salt and aluminum salt, add them into deionized water and mix them evenly to prepare magnesium-aluminum solution;
[0017] 2) Add sodium hydroxide, sodium benzenesulfonate, tetrabutyl phosphine hydroxide and sintering aid into deionized water and mix well to prepare alkaline solution;
[0018] 3) Add the magnesium aluminum solution and the alkali solution into the reaction container at the same time, stir at a high speed for 2-3 hours at a temperature of 60-90°C to obtain a colloidal precipitate, and then crystallize the colloidal precipitate, wash, filter and dry it.
[0019] By adopting the above technical solution, bauxite, jasper, coal gangue, iron ore and modified magnesium-aluminum hydrotalcite are used as sintering raw materials. Under high-temperature sintering conditions, elements such as magnesium and calcium can fill the pores of the mullite lattice, thereby increasing the skeleton strength of the ceramsite, ensuring the density of the overall particles, and thus improving the compressive strength of the ceramsite. In addition, after the magnesium-aluminum hydrotalcite is introduced into the sintering system, the magnesium and aluminum elements can diffuse and migrate to other metallized layers to form a sponge skeleton structure. At the same time, the crystal water molecules, benzenesulfonate ions and tetrabutylphosphonium ions in the interlayer structure of the magnesium-aluminum hydrotalcite will decompose to generate carbon dioxide and water vapor, thereby forming a uniform and fine microporous structure inside the ceramsite, while ensuring the skeleton strength of the ceramsite, obtaining a lower density, and better overall fracturing performance.
[0020] In addition, during the preparation of the modified magnesium-aluminum hydrotalcite, the co-precipitation of magnesium salt and aluminum salt is used to form a layered magnesium-aluminum hydrotalcite structure, and the interlayer spacing of the magnesium-aluminum hydrotalcite is increased under the expansion effect of sodium benzenesulfonate and tetrabutyl phosphine hydroxide. At this time, a part of the sintering aid will be intercalated into the interlayer structure of the modified magnesium-aluminum hydrotalcite, and the remaining sintering aid will be evenly wrapped on the surface of the magnesium-aluminum hydrotalcite particles to form a coating layer. In the early stage of the sintering process, the sintering aid in the coating layer can form a eutectic liquid phase to increase the mass transfer rate, and in the middle and late stages of sintering, the sintering aid intercalated in the interlayer structure also plays a good activation role, reduces the grain coarsening rate, and weakens the sintering interface bonding, thereby reducing the firing temperature and firing difficulty of the ceramsite, and obtaining a ceramsite support structure with better compressive performance and better mechanical properties.
[0021] Preferably, the sintering aid is one or more of nano-aluminum oxide, nano-zinc oxide, nano-magnesium oxide, nano-yttrium oxide, nano-titanium oxide, nano-molybdenum oxide, nano-calcium oxide, and nano-silicon dioxide.
[0022] By adopting the above technical solution, the types and composition of sintering aids are optimized and adjusted, the flow and mass transfer state of the liquid phase formed during sintering is improved, the abnormal growth of grains is inhibited, and the grain size distribution is made more uniform. In addition, the formed liquid phase can flow between the raw material particles, infiltrate and wrap the particle components, activate the lattice of crystals such as alumina, and produce a series of intermediate solid solutions, thereby reducing the sintering temperature and improving the strength of the ceramsite skeleton.
[0023] The sintering aids listed in this application can all achieve corresponding technical effects. More preferably, the sintering aid is at least one of nano-alumina and nano-yttrium oxide.
[0024] Preferably, the sintering aid is composed of nano-alumina and nano-yttrium oxide in a mass ratio of (12-15):(1.5-2).
[0025] By adopting the above technical scheme, testing and screening the composition ratio of the sintering aid, and using a compound of nano-alumina and nano-yttrium oxide, the solid solution reaction of alumina and yttrium oxide is promoted, which not only reduces the sintering temperature, but also improves the microporous structure of the sintered body to obtain higher compressive strength.
[0026] Preferably, the average particle size of the sintering aid is 1-6 nm.
[0027] By adopting the above technical solution, the sintering aid particles with larger particle size will reduce the intercalation amount in the layered structure, and the thickness of the coating layer will increase, which will not play a good sintering role in the middle and late stages of sintering. The sintering aid particles with smaller particle size are easy to agglomerate, and the increase in intercalation amount will lead to a poor sintering effect in the early stage. Therefore, the average particle size of the sintering aid is optimized and adjusted to balance the sintering effect in the early, middle and late stages of sintering, and obtain better mechanical properties.
[0028] Preferably, in step 1), nMg / nAl in the magnesium-aluminum solution is (3-5):1.
[0029] By adopting the above technical solution, the size of nMg / nAl in the modified magnesium-aluminum hydrotalcite is optimized and adjusted. On the one hand, the interlayer spacing of the modified magnesium-aluminum hydrotalcite can be adjusted, thereby regulating the interlayer insertion amount of the sintering aid. On the other hand, the removal rate of hydroxyl groups, bound water and benzenesulfonate anions on the layer plate can be regulated, thereby improving the microporous structure state of the ceramsite and obtaining better mechanical properties.
[0030] Preferably, the mass ratio of the modified magnesium aluminum hydrotalcite to bauxite is (0.16-0.165):1.
[0031] By adopting the above technical scheme, the mass ratio of modified magnesium-aluminum hydrotalcite to bauxite is tested and screened, more mullite crystal phase is generated under high-temperature sintering conditions, and the filling of elements such as magnesium and calcium into the mullite lattice is promoted, thereby further enhancing the strength of the ceramsite skeleton while lowering the firing temperature.
[0032] Preferably, the particle size of the modified magnesium aluminum hydrotalcite is 20-50 μm.
[0033] By adopting the above technical solution, when the particle size of the modified magnesium-aluminum hydrotalcite is too large, the sintering agent cannot form a uniform and complete coating layer structure, resulting in a poor sintering effect. When the particle size of the modified magnesium-aluminum hydrotalcite is too small, the intercalation amount decreases, and irregular agglomerates are easily formed between the sintering agent and the modified magnesium-aluminum hydrotalcite particles. Therefore, the particle size of the modified magnesium-aluminum hydrotalcite is optimized and adjusted to further improve the mechanical properties of the ceramsite sintered body.
[0034] In a second aspect, the present application provides a method for preparing a fracturing proppant using a magnesium-aluminum material as a raw material, using the following technical solution:
[0035] A method for preparing a fracturing proppant using a magnesium-aluminum material as a raw material comprises the following steps:
[0036] S1: taking a formulated amount of bauxite, slaked bauxite, coal gangue, modified magnesium-aluminum hydrotalcite and iron ore, mixing them and then ball-milling them to obtain raw material powder;
[0037] S2: the raw material powder is granulated into semi-finished granules, and then dried to obtain green compacts;
[0038] S3: The green body is sintered, sieved and sorted to obtain.
[0039] By adopting the above technical scheme, the raw materials are fully mixed and ball-milled to obtain raw material powder with uniform particle size distribution and appropriate discreteness, and then the raw material powder is subjected to a granulation process and dried to obtain a green body. Each powder particle after ball milling has a certain internal stress, which can be released during the sintering process, which is beneficial to increase the crystal contact area between particles, promote the migration and recrystallization of materials between particles, and can enhance the compressive strength of the expanded clay fracturing proppant to a certain extent.
[0040] Preferably, in step S3, the sintering temperature is 1200-1350°C.
[0041] By adopting the above technical scheme, the sintering temperature is optimized and adjusted. With the assistance of the modified magnesium-aluminum hydrotalcite component, the sintering temperature is reduced while ensuring the formation of the mullite crystal phase and the doped crystal phase, thereby balancing the sintering difficulty and mechanical properties of the ceramsite fracturing proppant.
[0042] In summary, this application has the following beneficial effects:
[0043] 1. Since the present application uses bauxite, jasper, coal gangue and other components in combination with modified magnesium-aluminum hydrotalcite, it plays a good role in assisting sintering during the sintering process, can effectively reduce the sintering temperature of the ceramsite fracturing proppant, and is conducive to the formation of various stable crystalline phase structures, thereby obtaining better mechanical properties.
[0044] 2. This application optimizes and adjusts the type and composition of the sintering aid, and adjusts the performance parameters of the modified magnesium-aluminum hydrotalcite, further improving the sintering effect, promoting the formation of mullite crystal phase, corundum crystal phase and doped crystal phase, reducing the difficulty of sintering the ceramsite body, and increasing the compressive strength.
[0045] 3. The fracturing proppant made of magnesium-aluminum material as raw material prepared by the preparation method of the present application has lower sintering difficulty and higher mechanical properties, and is suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 : Performance test data diagram of fracturing proppants using magnesium-aluminum materials as raw materials in Examples 1-5 and Comparative Examples 1-6 of the present application.
[0047] Figure 2 : SEM image of the modified magnesium-aluminum hydrotalcite of Example 5 of the present application. DETAILED DESCRIPTION
[0048] The present application is further described in detail below with reference to the embodiments.
[0049] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available. Example
[0050] Example 1
[0051] The fracturing proppant with magnesium-aluminum material as raw material in this embodiment is made of the following raw materials by weight percentage: 60% bauxite; 20% jasper; 5% coal gangue; 10% modified magnesium-aluminum hydrotalcite; 4% iron ore; and 1% waste ceramsite.
[0052] The modified magnesium aluminum hydrotalcite of this embodiment is prepared by a method comprising the following steps:
[0053] 1) Take magnesium nitrate and aluminum nitrate, add them into 10 kg of deionized water and mix them evenly to prepare a magnesium-aluminum solution, wherein nMg / nAl in the magnesium-aluminum solution is 2:1;
[0054] 2) Add 1.25kg of sodium hydroxide, 1.5kg of sodium benzenesulfonate, 0.3kg of tetrabutyl phosphine hydroxide and nano zinc oxide into 15kg of deionized water and mix well to make alkaline solution;
[0055] 3) The magnesium aluminum solution and the alkali solution are simultaneously dripped into the reaction kettle, and stirred at a speed of 5000 rpm / min for 3 hours at a temperature of 60°C to obtain a colloidal precipitate, and then the colloidal precipitate is placed in an oven for crystallization for 16 hours, and then washed with deionized water, filtered and dried to obtain the modified magnesium aluminum hydrotalcite with an average particle size of 100 μm.
[0056] The bauxite is secondary bauxite, and the sintering aid is nano zinc oxide with an average particle size of 10 nm.
[0057] The method for preparing a fracturing proppant using magnesium-aluminum material as raw material in this embodiment comprises the following steps:
[0058] S1: taking a formulated amount of bauxite, slaked bauxite, coal gangue, modified magnesium-aluminum hydrotalcite and iron ore, mixing them in a mixer and then feeding them into a ball mill to obtain raw material powder by a wet ball milling process;
[0059] S2: feeding the raw material powder into a granulator to form semi-finished granules by a semi-wet granulation process, and then drying to obtain a green body;
[0060] S3: The green body is sent into a rotary kiln for sintering at a sintering temperature of 1450°C and a sintering time of 4 hours, and then the defective products are screened and sorted to obtain the obtained ceramsite fracturing proppant with a specification of 20 / 40 mesh.
[0061] Example 2
[0062] The fracturing proppant with magnesium-aluminum material as raw material in this embodiment is made of the following raw materials by weight percentage: 50% bauxite; 30% jasper; 3% coal gangue; 8% modified magnesium-aluminum hydrotalcite; 6% iron ore; and 3% waste ceramsite.
[0063] The modified magnesium aluminum hydrotalcite of this embodiment is prepared by a method comprising the following steps:
[0064] 1) Take magnesium nitrate and aluminum nitrate, add them into 10 kg of deionized water and mix them evenly to prepare a magnesium-aluminum solution, wherein nMg / nAl in the magnesium-aluminum solution is 3:1;
[0065] 2) Add 1.25kg of sodium hydroxide, 1.5kg of sodium benzenesulfonate, 0.3kg of tetrabutyl phosphine hydroxide and nano zinc oxide into 15kg of deionized water and mix well to make alkaline solution;
[0066] 3) The magnesium aluminum solution and the alkali solution are simultaneously dripped into the reaction kettle, stirred at 7000 rpm / min for 2 hours at 80°C to obtain a colloidal precipitate, and then the colloidal precipitate is placed in an oven for crystallization for 20 hours, and then washed with deionized water, filtered and dried to obtain the modified magnesium aluminum hydrotalcite with an average particle size of 20 μm.
[0067] The bauxite is secondary bauxite and the sintering aid is nano silicon dioxide with an average particle size of 1 nm.
[0068] The method for preparing a fracturing proppant using magnesium-aluminum material as raw material in this embodiment comprises the following steps:
[0069] S1: taking a formulated amount of bauxite, slaked bauxite, coal gangue, modified magnesium-aluminum hydrotalcite and iron ore, mixing them in a mixer and then feeding them into a ball mill to obtain raw material powder by a wet ball milling process;
[0070] S2: feeding the raw material powder into a granulator to form semi-finished granules by a semi-wet granulation process, and then drying to obtain a green body;
[0071] S3: The green body is sent into a rotary kiln for sintering at a sintering temperature of 1350°C and a sintering time of 6 hours, and then the defective products are screened and sorted to obtain the obtained ceramsite fracturing proppant with a specification of 20 / 40 mesh.
[0072] Example 3
[0073] The fracturing proppant with magnesium-aluminum material as raw material in this embodiment is made of the following raw materials by weight percentage: 55% bauxite; 25% jasper; 3.5% coal gangue; 9% modified magnesium-aluminum hydrotalcite; 5.5% iron ore; and 2% waste ceramsite.
[0074] The modified magnesium aluminum hydrotalcite of this embodiment is prepared by a method comprising the following steps:
[0075] 1) Take magnesium nitrate and aluminum nitrate, add them into 10 kg of deionized water and mix them evenly to prepare a magnesium-aluminum solution, wherein nMg / nAl in the magnesium-aluminum solution is 5:1;
[0076] 2) Add 1.25kg of sodium hydroxide, 1.5kg of sodium benzenesulfonate, 0.3kg of tetrabutyl phosphine hydroxide and nano zinc oxide into 15kg of deionized water and mix well to make alkaline solution;
[0077] 3) The magnesium aluminum solution and the alkali solution are simultaneously dripped into the reaction kettle, stirred at 6500 rpm / min for 2 hours at 90°C to obtain a colloidal precipitate, and then the colloidal precipitate is placed in an oven for crystallization for 18 hours, and then washed with deionized water, filtered and dried to obtain the modified magnesium aluminum hydrotalcite with an average particle size of 50 μm.
[0078] The bauxite is secondary bauxite, and the sintering aid is nano-alumina with an average particle size of 6nm.
[0079] The method for preparing a fracturing proppant using magnesium-aluminum material as raw material in this embodiment comprises the following steps:
[0080] S1: taking a formulated amount of bauxite, slaked bauxite, coal gangue, modified magnesium-aluminum hydrotalcite and iron ore, mixing them in a mixer and then feeding them into a ball mill to obtain raw material powder by a wet ball milling process;
[0081] S2: feeding the raw material powder into a granulator to form semi-finished granules by a semi-wet granulation process, and then drying to obtain a green body;
[0082] S3: The green body is sent into a rotary kiln for sintering at a sintering temperature of 1200°C for 5 hours, and then the defective products are screened and sorted to obtain the obtained ceramsite fracturing proppant with a specification of 20 / 40 mesh.
[0083] Example 4
[0084] The fracturing proppant using magnesium-aluminum material as raw material in this embodiment is different from that in Example 3 in that in the preparation method of modified magnesium-aluminum hydrotalcite, the sintering aid is composed of nano-alumina and nano-yttrium oxide in a mass ratio of 15:2, and the rest is the same as in Example 3.
[0085] The average particle size of nano-alumina is 5nm, and the average particle size of nano-yttrium oxide is 10nm.
[0086] The preparation method of the fracturing proppant using magnesium-aluminum material as raw material in this embodiment is the same as that in Example 3.
[0087] Example 5
[0088] The fracturing proppant using magnesium-aluminum material as raw material in this embodiment is different from that in Embodiment 3 in that in the preparation method of modified magnesium-aluminum hydrotalcite, the sintering aid is composed of nano-alumina and nano-yttrium oxide in a mass ratio of 12:1.5, and the rest is the same as in Embodiment 3.
[0089] The average particle size of nano-alumina is 5nm, and the average particle size of nano-yttrium oxide is 10nm.
[0090] The preparation method of the fracturing proppant using magnesium-aluminum material as raw material in this embodiment is the same as that in Example 3.
[0091] Comparative Example
[0092] Comparative Example 1
[0093] The fracturing proppant with magnesium-aluminum material as raw material in this comparative example is made of the following raw materials by weight percentage: 60% bauxite; 20% jasper; 5% coal gangue; 10% magnesium-aluminum hydrotalcite; 4% iron ore; and 1% waste ceramsite.
[0094] The bauxite is secondary bauxite. The sintering aid is nano zinc oxide with an average particle size of 10 nm. The model of magnesium aluminum hydrotalcite is MA-503, and the manufacturer is Zhejiang Huate New Materials Co., Ltd.
[0095] The preparation method of the fracturing proppant using magnesium-aluminum material as raw material in this comparative example is different from that in Example 1 in that the modified magnesium-aluminum hydrotalcite in Example 1 is replaced by the magnesium-aluminum hydrotalcite mentioned above.
[0096] Comparative Example 2
[0097] The fracturing proppant with magnesium-aluminum material as raw material in this comparative example is made of the following raw materials by weight percentage: 60% bauxite; 20% jasper; 5% coal gangue; 10% magnesite; 4% iron ore; and 1% waste ceramsite.
[0098] The bauxite is secondary bauxite, and the sintering aid is nano zinc oxide with an average particle size of 10 nm.
[0099] The preparation method of the fracturing proppant using the magnesium-aluminum material as raw material in this comparative example is different from that in Example 1 in that the modified magnesium-aluminum hydrotalcite in Example 1 is replaced by the above-mentioned magnesite.
[0100] Comparative Example 3
[0101] The difference between the fracturing proppant using magnesium-aluminum material as raw material in this comparative example and that in Example 1 is that in the preparation method of the modified magnesium-aluminum hydrotalcite, no sintering aid is added in step 2), and the rest is the same as in Example 1.
[0102] The preparation method of the fracturing proppant using magnesium-aluminum material as raw material in this comparative example is the same as that in Example 1.
[0103] Comparative Example 4
[0104] The difference between the fracturing proppant using magnesium-aluminum material as raw material in this comparative example and that in Example 1 is that in the preparation method of the modified magnesium-aluminum hydrotalcite, sodium benzenesulfonate is not added in step 2), and the rest is the same as in Example 1.
[0105] The preparation method of the fracturing proppant using magnesium-aluminum material as raw material in this comparative example is the same as that in Example 1.
[0106] Comparative Example 5
[0107] The difference between the fracturing proppant using magnesium-aluminum material as raw material in this comparative example and that in Example 1 is that in the preparation method of the modified magnesium-aluminum hydrotalcite, tetrabutylphosphine hydroxide is not added in step 2), and the rest is the same as in Example 1.
[0108] The preparation method of the fracturing proppant using magnesium-aluminum material as raw material in this comparative example is the same as that in Example 1.
[0109] Comparative Example 6
[0110] The fracturing proppant using magnesium-aluminum material as raw material in this comparative example is different from that in Example 1 in that in the preparation method of modified magnesium-aluminum hydrotalcite, sodium dodecyl sulfate is used to replace tetrabutylphosphonium hydroxide in step 2), and the rest is the same as in Example 1.
[0111] The preparation method of the fracturing proppant using magnesium-aluminum material as raw material in this comparative example is the same as that in Example 1.
[0112] Performance testing
[0113] Detection Methods
[0114] The fracturing proppants made of magnesium-aluminum materials in Examples 1-5 and Comparative Examples 1-6 were tested for compressive strength using a pressure testing machine, with the force value controlled at 1000 N / s and the target force value at 250000 N. After the target was reached, the control channel was maintained for 120 s, and the sample was judged to be damaged; the volume density was tested according to SY / T5108-2014 "Proppant Performance Test Method for Hydraulic Fracturing and Gravel Packing Operations"; the modified magnesium-aluminum hydrotalcite in Example 6 was subjected to SEM analysis, and the comprehensive test results are as follows: Figure 1 and Figure 2 shown.
[0115] Analyze Examples 1-3 and combine Figure 1It can be seen that the present application adopts modified magnesium-aluminum hydrotalcite as the magnesium-aluminum material, which can form a sintering-promoting liquid phase during the sintering process, and has a good wrapping and infiltration effect on the powder particles of other components, promoting element migration and crystallization between the particles, and is beneficial to the formation of mullite crystal phase, corundum crystal phase and other doped crystal phases, so as to obtain a complete and uniform ceramsite skeleton support structure with high compressive strength. In addition, the modified magnesium-aluminum hydrotalcite component also produces a large amount of gaseous substances during the sintering process, which can form a micro-nano pore structure in the ceramsite, thereby further improving the mechanical properties of the product while reducing the density. It can be seen that the compressive strength of Example 3 can reach more than 110KN.
[0116] Analyze Example 1 and Comparative Examples 1-6 and combine Figure 1 It can be seen that the conventional magnesium-aluminum hydrotalcite used in Comparative Example 1 can only provide magnesium and aluminum elements in the sintering stage, and will also increase the difficulty of sintering, resulting in poor mechanical properties of the sintered ceramsite. After the modified magnesium-aluminum hydrotalcite was replaced by magnesite in Comparative Example 2, although the melting point of magnesite is relatively low, only about 1000 degrees, it can play a certain sintering effect in the early stage of sintering, but it has no effect in the middle and late stages of sintering, resulting in poor mechanical properties of the sintered ceramsite. In Comparative Example 3, no sintering aid was added, which can only play a certain role in releasing gaseous substances, and in addition, without the assistance of the sintering effect, the formed microporous structure is not uniform and perfect, and the compressive strength is reduced relative to that of Example 1. Sodium benzenesulfonate and tetrabutyl phosphine hydroxide were not added in Comparative Examples 4 and 5, resulting in an imbalance between the amount of intercalation and the amount of coating, and a decrease in the overall sintering effect, thereby affecting the mechanical properties of the sintered ceramsite. In Comparative Example 6, sodium dodecyl sulfate was used to replace tetrabutyl phosphine hydroxide. The reason for the decrease in the compressive strength of the sintered ceramsite may be that the adsorption and bonding anisotropy of sodium dodecyl sulfate on the layer plate is large, and the uniformity of the interlayer structure becomes poor, which leads to large fluctuations in the interlayer insertion amount at different positions.
[0117] Analyze Examples 1-3, Examples 4-5 and combine Figure 1 and Figure 2 It can be seen that by optimizing and adjusting the preparation process of modified magnesium-aluminum hydrotalcite, optimizing and adjusting the reaction temperature, the composition ratio of the sintering agent and the ratio of nMg / nAl in the magnesium-aluminum solution, the distribution state of the sintering agent is further improved, and the ratio of the intercalation amount and the coating amount is balanced. Figure 2 It can be seen that the modified magnesium-aluminum hydrotalcite of Example 5 has a very uniform interlayer morphology, thereby obtaining a better sintering effect, which is beneficial to improving the microscopic state of the sintered ceramsite body and enhancing the mechanical properties of the product. It can be seen that the compressive strength of Example 5 can reach more than 120KN.
[0118] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A fracturing proppant made of magnesium-aluminum material, characterized in that: By weight percentage, it is made from the following raw materials: Bauxite 50-60%; Jadeite 20-30%; Coal gangue 3-5%; Modified magnesium aluminum hydrotalcite 8-10%; Iron ore 4-6%; The remainder is waste ceramsite; The modified magnesium aluminum hydrotalcite is prepared by a method comprising the following steps: 1) Take magnesium salt and aluminum salt, add them into deionized water and mix them evenly to prepare magnesium-aluminum solution; 2) Add sodium hydroxide, sodium benzenesulfonate, tetrabutyl phosphine hydroxide and sintering aid into deionized water and mix well to prepare alkaline solution; 3) Add the magnesium aluminum solution and the alkali solution into the reaction container at the same time, stir at high speed for 2-3 hours at a temperature of 60-90°C to obtain a colloidal precipitate, and then crystallize the colloidal precipitate, wash, filter and dry it; The sintering aid is composed of nano-alumina and nano-yttrium oxide in a mass ratio of (12-15):(1.5-2); The average particle size of the sintering aid is 1-6 nm; In the step 1), nMg / nAl in the magnesium-aluminum solution is (3-5):1; The mass ratio of the modified magnesium aluminum hydrotalcite to bauxite is (0.16-0.165):1; The particle size of the modified magnesium aluminum hydrotalcite is 20-50 μm.
2. A method for preparing a fracturing proppant using magnesium-aluminum material as raw material as claimed in claim 1, characterized in that: The steps include: S1: taking a formulated amount of bauxite, slaked bauxite, coal gangue, modified magnesium-aluminum hydrotalcite and iron ore, mixing them and then ball-milling them to obtain raw material powder; S2: the raw material powder is granulated into semi-finished granules, and then dried to obtain green compacts; S3: The green body is sintered, sieved and sorted to obtain.
3. The method for preparing a fracturing proppant using magnesium-aluminum material as raw material according to claim 2, characterized in that: In the step S3, the sintering temperature is 1200-1350°C.
Citation Information
Patent Citations
Preparation method of low-cost petroleum fracturing propping agent
CN103725281A
Process for preparing ceramsite proppant by using magnesium slag and ceramsite proppant
CN104560006A